Prevalence of low scores on language tests as a potential factor in misdiagnosis of cognitive impairment in a Spanish-speaking adult population. Issue 1 (2nd January 2022) - Olabarrieta-Landa, Laiene; Ramos Usuga, Daniela; Rivera, Diego; Leal, Giselle; Bailey, K. Chase; Calderón Chagualá, Amilkar; Rabago, Brenda; Esenarro, Loida; Mascialino, Guido; Arango-Lasprilla, Juan Carlos
Abstract: Objective: In this study, the prevalence of low scores for two neuropsychological tests of language has been determined. Methods: In total, N  = 5218 healthy adults from 11 countries in Latin America (LA) were administered the Boston Naming Test (BNT) and the Verbal Fluency Test (VFT) as part of a comprehensive neuropsychological evaluation. Z -scores were calculated for BNT Total score, and phonological (letters F, A, S, M ) and semantic (Animals, Fruits). Scores were adjusted for age, age 2, sex, education, and interaction variables if significant for the given country. Each Z -score was converted to a percentile for each of the seven test-scores. Each participant was categorized based on his/her number of low scoring tests in specific percentile cutoff groups (25th, 16th, 10th, 5th, and 2nd). Results: Between 53% (Paraguay) and 71% (Mexico) of the sample had at least 1-score below the 25th percentile, and between 41% (Paraguay) and 55% (Cuba) scored below the 16th percentile. Between 27% (Paraguay) and 39% (Peru) scored below the 10th percentile on at least 1-score, and between 17% (Chile) and 23% (Argentina) scored below the 5th percentile. Conclusions: Clinicians should use these data to reduce false-positive diagnoses and to improve the neuropsychological assessments in Spanish-speaking individuals from LA countries.